Analysis of the Debate Around Religious Pluralism in Indonesia - Siti Rahmah; Asep Abdul Muhyi (UIN Sunan Gunung Djati Bandung, 2021)
This study aims to discuss the thoughts of religious pluralism (interreligious relations). This research is a type of qualitative research that applies literature study. Here the authors collect data from books and journals relevant to the research title. The findings and discussion of this study include the thought of kalam in Islam, religious pluralism and analysis of debates around religious pluralism. This research concludes, based on existing references that religious pluralism is not a solution to the diversity of religions and the harmony of human life. However, pluralism has even sparked new inter-religious debates that force their understanding to equalize all religions. In fact, the concept of each religion is clearly different and cannot be equated. This study recommends further research on the thought of religious pluralism from various perspectives.